The roles of the potassium-uptake systems, Trk and Kdp, in the extracellular and intracellular growth of Mycobacterium tuberculosis - Cholo, Moloko C. (University of Pretoria, 2020)
Thesis (PhD (Medical Immunology))--University of Pretoria, 2020.